The role of environmental factors in search and rescue incidents in Nunavut, Canada. (August 2016) - Clark, D.G.; Ford, J.D.; Berrang-Ford, L.; Pearce, T.; Kowal, S.; Gough, W.A.
Abstract: Objectives: Unintentional injury is a leading cause of morbidity and mortality in Nunavut, where the importance of land-based activities and reliance on semi-permanent trails create unique risk profiles. Climate change is believed to be exacerbating these risks, although no studies have quantitatively examined links between environmental conditions and injury and distress in the Canadian Arctic. We examine the correlation between environmental conditions and land-based search and rescue (SAR) incidents across Nunavut. Study design: Case study. Methods: Case data were acquired from the Canadian National Search and Rescue Secretariat. Gasoline sales from across the territory are then used to model land-use and exposure. We compare weather and ice conditions during 202 SAR incidents to conditions during 755 non-SAR days (controls) between 2013 and 2014. Results: We show daily ambient temperature, ice concentration, ice thickness, and variation in types of ice to be correlated with SAR rates across the territory during the study period. Conclusions: These conditions are projected to be affected by future climate change, which could increase demand for SAR and increase injury rates in the absence of targeted efforts aimed at prevention and treatment. This study provides health practitioners and public health communities with clearer understanding to prepare, respond to, and prevent injuries across the Arctic. Highlights: The use of gasoline sales is proposed as a control for hazard exposure and land-use. Environmental conditions of days with a search and rescue (SAR) event are compared to conditions of control days. Ice conditions and daily temperatures are shown to influence risk of SAR and injury.